2021
DOI: 10.1021/acs.jafc.1c03301
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG Ameliorated Long-Term Exposure to TiO2 Nanoparticles Induced Microbiota-Mediated Liver and Colon Inflammation and Fructose-Caused Metabolic Abnormality in Metabolism Syndrome Mice

Abstract: A huge number of titanium dioxide nanoparticles (TiO 2 NPs) exist in confectionery foods, which is a high-risk factor for development of diet-induced metabolism syndrome (MetS). In this study, we built a high fructose drinking-induced MetS mouse model, and oral intake of 20 mg/kg TiO 2 NPs was administered for 8 weeks. Significant pathological changes and inflammatory factors of overproduction were detected in the liver and colon. The 16S rDNA sequencing analysis results indicated that TiO 2 NPs evidently and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Desulfovibrionaceae is one sulfate-reducing bacteria and produces metabolites H 2 S [ 28 ]. A number of studies showed that Desulfovibrionaceae could induce inflammation, injury gut mucosa, and decrease of colon barrier function [ 20 , 29 , 30 ]. Similarly, Luo et al reported that the relative abundance of Desulfovibrionaceae was found to increase in the AOM/DSS-induced colon cancer mice and decrease due to the treatment of Ganoderma lucidum polysaccharide [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Desulfovibrionaceae is one sulfate-reducing bacteria and produces metabolites H 2 S [ 28 ]. A number of studies showed that Desulfovibrionaceae could induce inflammation, injury gut mucosa, and decrease of colon barrier function [ 20 , 29 , 30 ]. Similarly, Luo et al reported that the relative abundance of Desulfovibrionaceae was found to increase in the AOM/DSS-induced colon cancer mice and decrease due to the treatment of Ganoderma lucidum polysaccharide [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from the ovary was isolated and reverse transcribed into cDNA according to the techniques described in the previous work. 29 Primer Express Software (Applied Biosystems, Foster City, CA, USA) was used to design the primers, which were then manufactured by TSINGKE Biological Technology (Beijing, China). Table S1 contains the primer sequences.…”
Section: Methodsmentioning
confidence: 99%
“…According to the results presented in previous studies, in 2011, Fuenmayor et al assessed the conditions required for a better BP fermentation from Columbia. Their results showed the possibility to use L. acidophilus inoculum in a matrix of BP to induce lactic fermentation and generate a probiotic product with additional functional characteristics, which might be used as a protein food supplement suitable for human consumption or as an ingredient in the development of other functional foods ( 98 ).…”
Section: Potential Therapeutic Properties Of Labs Found In Bb And/or ...mentioning
confidence: 99%